THE DETERMINANTS OF POVERTY IN THE MEKONG RIVER DELTA KEY ECONOMIC ZONE IN VIETNAM - Ngoc, Le Thanh; Diem, Pham Thi Thuy (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
This paper investigates the determinants of poverty in Mekong River Delta Key Economic Zone in Vietnam for a sample of 604 households in Can Tho province, An Giang province, KienGiang province and Ca Mau province in 2012. Explanatory variables include demographic, nature, region, finance and physical. Using Binary Logistics regression, results show the complexity of the issues, wherein the financial variable has been the most important influence of poverty in this area.